2017
DOI: 10.1016/j.jdermsci.2017.07.011
|View full text |Cite
|
Sign up to set email alerts
|

In vivo confocal Raman spectroscopy for intrinsic aging and photoaging assessment

Abstract: The wavenumber region between 798 and 994cm is useful for the analysis of dermal collagen alterations through the intrinsic aging process, while photoaging is better assessed by the I/I intensities ratio. This is the first skin aging study to show a correlation between Raman peaks and the amount of collagen assessed by HFUS and histology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Confocal Raman microscopy (CRM) is a powerful non‐invasive tool to measure depth profiles of molecular components in the SC , in which the skin components are measured depth‐dependently in vivo / ex vivo at high spatial resolution. An area of interest using CRM in dermatology is the analysis of the penetration into the skin , the skin barrier function provided by the SC , and collagen of the dermis . Our group recently introduced methods to determine the molecular properties of skin barrier function‐related parameters, such as water bonding states , ICL ordering and secondary and tertiary structures of keratin in the SC in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Confocal Raman microscopy (CRM) is a powerful non‐invasive tool to measure depth profiles of molecular components in the SC , in which the skin components are measured depth‐dependently in vivo / ex vivo at high spatial resolution. An area of interest using CRM in dermatology is the analysis of the penetration into the skin , the skin barrier function provided by the SC , and collagen of the dermis . Our group recently introduced methods to determine the molecular properties of skin barrier function‐related parameters, such as water bonding states , ICL ordering and secondary and tertiary structures of keratin in the SC in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…On the papillary dermis, we also observed that chronological aging was associated with a decrease of the 938/922 ratio. This result is in agreement with a recent study performed in vivo on the papillary dermis, where de Vasconcelos Nasser Caetano et al attributed the reduction of the 855 cm −1 and 938 cm −1 band intensities to collagen alterations during intrinsic aging. Zhang et al showed that the 938 cm −1 band provides a measurement of the collagen highly bonded with water .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, identification of Raman spectral bands for collagen has already been performed by several teams . This is a very suitable technique for determining molecular and structural modifications occurring during biological process such as skin aging . Gniadecka et al studied the water and protein structure in photoaged and chronically aged skin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peak assignment (Movasaghi et al 2007) Bai et al intrinsic aging and photoaging in vivo in 15 subjects between 28 and 82 years of age, divided into three different groups (de Vasconcelos Nasser Caetano et al 2017). The authors pointed out the prolinehydroxyproline region (intensities of peaks at 855 cm −1 and 938 cm −1 ) as suitable for the evaluation of intrinsic skin aging.…”
Section: Spectral Regionmentioning
confidence: 99%